Regulation of flavonoids in strawberry fruits by FaMYB5/FaMYB10 dominated MYB-bHLH-WD40 ternary complexes - Yue, Maolan; Jiang, Leiyu; Zhang, Nating; Zhang, Lianxi; Liu, Yongqiang; Lin, Yuanxiu; Zhang, Yunting; Luo, Ya; Zhang, Yong; Wang, Yan; Li, Mengyao; Wang, Xiaorong; et al. (Frontiers in Plant Science, 2023)
Anthocyanins endowing strawberry fruit red color are regulated by the MYB-bHLH-WD40 complex. By analyzing the MYBs involved in the flavonoid biosynthesis in strawberry, we found that R2R3-FaMYB5 promoted the content of anthocyanin and proanthocyanidins in strawberry fruits. Yeast two-hybrid and BiFC assays confirmed that MBW complexes connected with flavonoid metabolism were FaMYB5/FaMYB10-FaEGL3 (bHLH)-FaLWD1/FaLWD1-like (WD40). Transient overexpression and qRT-PCR analysis revealed that disparate MBW models hold different patterns in the regulation of flavonoid biosynthesis in strawberry fruits. Compared with FaMYB10, FaMYB5 and its dominant complexes showed a more specific regulatory range on strawberry flavonoid biosynthetic pathway, while FaMYB10 was more extensive. In addition, the complexes involved in FaMYB5 facilitated PAs accumulation primarily through the LAR tributary while FaMYB10 mainly by the ANR branch. FaMYB9 and FaMYB11 tremendously elicited the accumulation of proanthocyanidins by up-regulating the expression levels of both LAR and ANR, and also affected anthocyanin metabolism by changing the ratio of Cy3G and Pg3G which were constituted as two major anthocyanin monomers in strawberries. Our study also illustrated that FaMYB5-FaEGL3-FaLWD1-like directly targeted the promoters of F3′H, LAR, and AHA10 thus committing to flavonoid accumulation. These results allow the specific members involved in the MBW complex to be deciphered and provide new insights into the regulatory mechanisms of anthocyanins and proanthocyanidins regulated by the MBW complex.